Recuperação judicial: uma análise empírica dos processos de recuperação judicial distribuídos junto à 2º Vara de Falência e Recuperações Judiciais do Foro Cível Central da Comarca da Capital do Estado de São Paulo, com ênfase nas recuperações judiciais encerradas por cumprimento - Oliveira, Rafael Alves de (2015)
The present work has as objective verify how many businessmen or business society that, after the closure of your respective judicial reorganization for the plan’s compliance, raised your respective business activities. As verification criterion uses the non posterior bankruptcy request or the judicial instrument enforcement originary of the judicial reorganization concession (article 59, 1st §, LRE) after the closure by plan’s compliance. Trying to achieve this objective, it was used and analyzed all the judicial reorganization requests distributed to the 2nd Bankruptcy and Judicial Reorganization Court of São Paulo, since the effectiveness of LRE (09/06/2005) until the temporal closure of this research, which is, 21st , October 2014. Subsidiary, in this research was done the description of the processes present in the specific research universe, identifying, therefore, data as the mean time of the judicial reorganization process steps, type of business and company size, reasons that lead to the processing dismissal, conversion in bankruptcy of the respective judicial reorganizations, quantity of granted reorganization and conceded, since these informations concern directly to this work’s final objective and compose previous moment to the future closure, as well as the data presented here can influence directly to the research conclusion. The presupposition that originate and guided this work is the absence of empiric data about the topic, because this research believes that the knowledge of the studied institute’s practical reality is necessary to understand and improve its functioning.